Biotransformation Of Valencene Utilizing Yarrowia Lipolytica In Buffer Systems - Zulkifli, Umy Aliya (Universiti Sains Malaysia, 2022)
Biotransformation is the process through which the functional groups of organic compounds are modified by living cells to a chemically different product. The procedure investigates the unique qualities of biological catalysts, such as stereospecificity and area specificity, as well as their capacity to endure reactions at no severe temperatures or pH values. In the biotransformation of (+)-valencene to produce (+)-nootkatone, Y. lipolytica is used as a biocatalyst for the oxidation of barely soluble hydrophobic steroids. The parameters such as in disodium phosphate and monosodium phosphate buffer system are manipulated to determine the optimum condition for (+)-nootkatone synthesis. GC-MS analysis was used to detect the results or the peak area of (+)- nootkatone and (+)- valencene. The growth curve of Y. lipolytica was determined, and the best growth phase for biotransformation was in the exponential phase at 22 h. The maximum Wdcw concentration is 5.70 g/L was observed at 55 h in the stationary phase. Biotransformation of (+)-valencene utilizing Y. lipolytica in buffer systems is done successfully. The maximum (+)- nootkatone area was observed at pH 6 by adding 250 μL (+)- valencene and cultivating at 30 ℃, 150 rpm. This study concludes that the buffer system's pH significantly impacts the utilization of yeast, Y. lipolytica, during biotransformation. The optimal pH for the fastest reaction rate and maximum production for the created cultures were discovered. The (+)- nootkatone production has been studied at pH 6, and it has the most significant peak compared to the others.